Gryllotalpa chrysea sp. nov., a new species of Mole Cricket (Orthoptera: Gryllotalpidae: Gryllotalpinae) from China - Wang, Ning; Yuan, Wei; Zhang, Tao; Gu, Jun-Jie; Ma, Li-Bin (Zootaxa, 2024)
A new species, Gryllotalpa chrysea sp. nov., distributed in Sichuan and Guangdong provinces of China is described. The body of the new species is small and easily distinguished from other species in the genus by its coloration of black body and golden forewings. Here, we describe and illustrate this new taxon, and provide description and illustration of the genitalia features of Gryllotalpa orientalis Burmeister, 1838 and Gryllotalpa cycloptera Ma & Zhang, 2011.